2013
DOI: 10.3389/fnhum.2013.00795
|View full text |Cite
|
Sign up to set email alerts
|

Does that look heavy to you? Perceived weight judgment in lifting actions in younger and older adults

Abstract: When interpreting other people's movements or actions, observers may not only rely on the visual cues available in the observed movement, but they may also be able to “put themselves in the other person's shoes” by engaging brain systems involved in both “mentalizing” and motor simulation. The ageing process brings changes in both perceptual and motor abilities, yet little is known about how these changes may affect the ability to accurately interpret other people's actions. Here we investigated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
3
16
1
1
Order By: Relevance
“…Aging decreases the efficiency in learning and then executing novel motor sequences ( Coats et al, 2013 ) with specific losses for action observation ( Maryott and Sekuler, 2009 ). For instance, Maguinness et al (2013) explored age-related differences in a task in which participants viewed videos of either a hand or a full body lifting weighted boxes and had to indicate the amount of weight being lifted. Older adults were overall less sensitive for weight prediction than young adults, but particularly so when there were fewer visual details on the biomechanics of the lift.…”
Section: Embodiment In Mental Representationsmentioning
confidence: 99%
“…Aging decreases the efficiency in learning and then executing novel motor sequences ( Coats et al, 2013 ) with specific losses for action observation ( Maryott and Sekuler, 2009 ). For instance, Maguinness et al (2013) explored age-related differences in a task in which participants viewed videos of either a hand or a full body lifting weighted boxes and had to indicate the amount of weight being lifted. Older adults were overall less sensitive for weight prediction than young adults, but particularly so when there were fewer visual details on the biomechanics of the lift.…”
Section: Embodiment In Mental Representationsmentioning
confidence: 99%
“…Previous laboratory studies have shown that humans are very sensitive to kinematics variations of biological movements and are able to accurately – though often implicitly – anticipate a lot of information from movement observations. An object’s weight for instance can be evaluated through movement kinematics of a partner manipulating a (non-visible) object (Maguinness, Setti, Roudaia, & Kenny, 2013 ; Meulenbroek, Bosga, Hulstijn, & Miedl, 2007 ; Runeson & Frykholm, 1983 ). It is also possible to detect the deceptive intentions of a person performing an object-related action or even to have an idea of what weight the actor expected the object to be (Runeson & Frykholm, 1983 ).…”
Section: Are Humans Sensitive To Socially-induced Modulation Of Motormentioning
confidence: 99%
“…Therefore, better physical health and enhanced dexterity should also facilitate and even enhance action/motor simulation in cognitive processing and reversely. For instance, healthy elderly are less accurate than younger adults in the estimation of perceived weight judgment (Maguinness et al, 2013 ). This effect of aging can be partly explained in terms of motor simulation, in other words as a function of the real or perceived motor-efficacy of elderly adults (see Potter et al, 2009 , for perceived efficacy).…”
Section: Action Motor Components and Cognition In Agingmentioning
confidence: 99%